PENGARUH LINGKUNGAN KERJA FISIK DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT BHAKTI KARYA DI SAWANGAN KOTA DEPOK - Rahmad Hidayat; Andi Sopandi (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
environment and work motivation on employee performance at PT Bhakti Karya in Sawangan, Depok City, both partially and simultaneously. This research employs a quantitative associative method. The population of this study includes all employees of PT Bhakti Karya in Sawangan, Depok City, with a sample size of 63 respondents. The data analysis techniques used in this research include simple linear regression, multiple linear regression, correlation coefficient, coefficient of determination, partial t-test, and simultaneous F-test. The results show that the physical work environment has a positive and significant effect on employee performance at PT Bhakti Karya in Sawangan, Depok City. This is evidenced by a correlation value of 0.913 (very strong relationship), a coefficient of determination of 83.3%, and a t-value of 3.327 > 1.999 with a significance level of 0.000 < 0.05. Furthermore, work motivation also has a positive and significant effect on employee performance, as indicated by a correlation value of 0.926 (very strong relationship), a coefficient of determination of 85.8%, and a t-value of 4.818 > 1.999 with a significance level of 0.000 < 0.05. Simultaneously, the physical work environment and work motivation have a positive and significant impact on employee performance at PT Bhakti Karya in Sawangan, Depok City. This is demonstrated by the multiple linear regression equation Y = 8.709 + 0.348X1 + 0.474X2, a correlation value of 0.938 (very strong relationship), a coefficient of determination of 88%, and an F-value of 219.373 > 3.15 with a significance level of 0.001 < 0.05. Keywords: Physical Work Environment, Work Motivation, Employee Performance